Comparison of "high throughput" micromethods for determination of cytochrome P450 activities with classical methods using HPLC for product identification - Anzenbacherová, Eva; Veinlichová, A; Mašek, Vlastimil; Anzenbacher, Pavel (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2005)
Enzyme activities of the CYP enzymes (CYP3A4, CYP2C9 and CYP2A6) were determined using classical substrates (testosterone, diclofenac and coumarin, respectively) as well as with luminogenic or fluorogenic substrates in micromethod arrangement. The luciferin-based luminogenic substrates for CYP3A4 and CYP2C9 as well as coumarin in micromethod for assay of CYP2A6 activity gave results well comparable with the classical methods with determination of reaction products by the HPLC.
Keywords: Cytochrome P-450 CYP3A; diklofenak; testosteron; vysokoúčinná kapalinová chromatografie; lidé; cytochrom P-450 CYP3A; Coumarins; Mixed Function Oxygenases; kumariny; Chromatography, High Pressure Liquid; Male; Diclofenac; Aryl Hydrocarbon Hydroxylases; systém (enzymů) cytochromů P-450; Testosterone; mužské pohlaví; oxygenasy se smíšenou funkcí; Cytochrome P-450 Enzyme System; aromatické hydroxylasy; Humans